PERAN E-COMMERCE TERHADAP PERILAKU KONSUMSI DAN KEPUTUSAN PEMBELIAN BUSANA ADAT MENJELANG HARI RAYA - Asmara Yanti, Ni Nyoman Suli (Waisya : Jurnal Ekonomi Hindu, 2024)
This research aims to describe the role of e-commerce in the consumption behavior of Hindu teenagers before the holidays and the role of e-commerce in purchasing decisions about Balinese traditional clothing. The research method used is descriptive qualitative by describing the results of interviews conducted with informants. The results found in this research indicate that E-commerce has an important role in influencing teenagers' consumption behavior before the holidays. There are several factors that influence teenagers' consumptive behavior before the holidays, including cultural factors, personal factors, social factors and psychological factors. E-commerce has an important role in helping Hindu teenagers decide to purchase Balinese traditional clothing before the holidays. There are several stages that teenagers go through before and until they decide to purchase a product. The stages of decision making to purchase Balinese traditional clothing are problem identification, information search, evaluation of alternatives from various e-commerce options, making a purchase and post-purchase product evaluation.